Hak-Hak Perempuan Dalam Surat Al-Ahzab (Tafsir Muqarin Al-Qurthubi dan Sayyid Quthb) - Shopiyah, Siti (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2023)
Islamic society has understood the verses relating to men and women in a way that favors men over women. Then Islam came to raise the dignity of women, so that today their position is equal between women and men. Women in their human nature and their rights get reasonable as men. Sayyid Quthb and Al-Qurthubi, the two generations of mufassir give different interpretations, this is because they have different styles. Based on the description above, this research focuses on two issues, namely: How is the interpretation of Sayyid Quthb and Al-Qurthubi on QS. AlAhzab: 33?. This research is a literature review. The data in this study were obtained from the book of Tafsir Fī Dzilālil Qur'ān and the book of Tafsir Al-Jami' Li Ahkam Al-Qur'an and several books that talk about women. The research method used is descriptive analytical. After the sources are collected, read, studied, understood, then analyzed descriptively comparative analytics through an inductive thought process. The conclusion of this study is that in the interpretation of the verses above Al-Qurtubi interprets women should stay in their homes, unless they are in a very emergency condition that requires them to leave the house. Furthermore, if the woman has to leave the house, then it should be noted that women should not adorn themselves excessively. Sayyid Quthb interprets that: If a wife is found to have completed domestic work at home well, then women may work outside the home, namely work that is good for women and does not contain negative effects. Then for wives who have fulfilled their needs, it can be enough to stay at home or if they still decide to work, then the intention is to practice knowledge or to worship.